ID 179 – Alpha-synuclein accumulation induced changes in white and gray matter detected by diffusion kurtosis imaging in TNWT-61 mouse model of Parkinson's disease. Issue 3 (March 2016) - Khairnar, A.; Kucerova, J.; Drazanova, E.; Latta, P.; Szabó, N.; Arab, A.; Hutter-Paier, B.; Havas, D.; Windisch, M.; Sulcova, A.; Starcuk, Z.; Király, A.; et al.
Abstract : Introduction: DKI by measuring non-Gaussian diffusion may better characterize the microstructural brain changes as compared to traditional DTI. The aim was to evaluate the capability of DKI for detecting the microstructural changes induced by alpha-synuclein accumulation in TNWT-61 mice using the tract based spatial statistics (TBSS) and region of interest (ROI) analyses. Methods: Fourteen month old TNWT-61 mice and wild-type (WT) littermates underwent DKI scanning using 9.4 Tesla MRI system in vivo . TBSS and ROI analysis was performed to detect the changes in white and gray matter in TNWT-61 and WT mice. Immunohistochemistry for alpha-synuclein was performed in 5 TNWT-61 mice and correlated with DKI findings. Results: The principle findings of this study were increase in mean kurtosis and decrease in mean diffusivity in thalamus, sensorimotor cortex, hippocampus, external capsule and basolateral amygdaloid nucleus in 14 month TNWT-61 mice as compared to WT littermates. We also found significant correlations between alpha-synuclein accumulation and increase in kurtosis and decrease in diffusivity in the thalamus. Conclusion: Our results reveal that DKI is sensitive in detecting microstructural changes due to alpha-synuclein accumulation in both GM and WM. These findings suggest that in PD patients DKI should be preferred to routine DTI despite a longer acquisition protocol.